Phenolic from residues of coffee: optimization of the process of extraction - Marcelo-Diaz, R. (2017)
The coffee industry, coffee shops and restaurants are in constant expansion and growth. Consequently, large amounts of Spent Coffee Grounds (SCG) are generated, which are solid coffee residues obtained after the ground coffee leaching process. This residue can be reused because of its compounds as phenolics. The objective of the present study was to evaluate the effect of extraction time (30-90 min) assisted by ultrasound (45kHz and 50 W), liquid-solid ratio (10-40 ml/g) and ethanol concentration (20-93.8%) in the total phenolic compounds (CFT) content expressed as mg gallic acid/g SCG dry matter. Surface response methodology (MSR) was used, as an eﬃcient technique that minimizes the number of experiments, through the central rotational compound design (DCCR) to determine the effect of these 3 factors and to perform the optimization of the extraction process conditions of total phenolic compounds. The predictions of the model were correlated with the experimental values in 84.04%, where there was a strong influence (P <0.05) of the ultrasound-assisted extraction time variables and liquid- solid ratio in the results. Optimal conditions (21.03% ethanol at a liquid-solid ratio of 11.65 ml/g SCG and ultrasonic assisted processing for 32.42 minutes) allowed a total phenolic compound content of 1429.09 mg AG/g of SCG to be obtained, a content higher than Obtained by other extraction techniques reported in the literature.